2011
DOI: 10.4049/jimmunol.1001567
|View full text |Cite
|
Sign up to set email alerts
|

A2B Adenosine Receptor Blockade Enhances Macrophage-Mediated Bacterial Phagocytosis and Improves Polymicrobial Sepsis Survival in Mice

Abstract: Antimicrobial treatment strategies must improve to reduce the high mortality rates in septic patients. In noninfectious models of acute inflammation, activation of A2B adenosine receptors (A2BR) in extracellular adenosine-rich microenvironments causes immunosuppression. We examined A2BR in antibacterial responses in the cecal ligation and puncture (CLP) model of sepsis. Antagonism of A2BR significantly increased survival, enhanced bacterial phagocytosis, and decreased IL-6 and MIP-2 (a CXC chemokine) levels af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 49 publications
5
92
0
Order By: Relevance
“…Our data are consistent with previous reports suggesting a role for A2bR-mediated immunosuppression [48][49][50] and implicating the A2aR as the major adenosine receptor involved in IL-10 induction in macrophages. 51 Interestingly, both the A2aR and A2bR are G-protein coupled receptors associated with the Gas subunit and are capable of activating adenylate cyclase and enhancing intracellular cyclic AMP (cAMP) levels.…”
Section: Discussionsupporting
confidence: 83%
“…Our data are consistent with previous reports suggesting a role for A2bR-mediated immunosuppression [48][49][50] and implicating the A2aR as the major adenosine receptor involved in IL-10 induction in macrophages. 51 Interestingly, both the A2aR and A2bR are G-protein coupled receptors associated with the Gas subunit and are capable of activating adenylate cyclase and enhancing intracellular cyclic AMP (cAMP) levels.…”
Section: Discussionsupporting
confidence: 83%
“…We did not observe an increase in oxidative burst in A 2B R-deficient neutrophils; our results may represent cross-talk between neutrophil adenosine receptors, with maintenance of A 2A R signaling in A 2B R -/-neutrophils, because A 2A R activation strongly inhibits oxidative burst (9,18). Our study also relates to work demonstrating that A 2B R-deficient macrophages exhibit enhanced phagocytosis and bacterial clearance in a model of sepsis (35). This study concluded that A 2B R -/-neutrophils did not demonstrate enhanced antibacterial activity, but only phagocytic capacity as a measure of bactericidal activity.…”
Section: Discussionsupporting
confidence: 63%
“…Studies of adenosine receptor signaling in animal models of intraperitoneal sepsis have reported contradictory findings: A 2B R deletion was found to increase expression of inflammatory cytokines and worsened survival (40); conversely, A 2B R blockade, global deletion, or selective deletion from myeloid cells was associated with accelerated bacterial clearance and improved outcome (35). Because unchecked inflammation and failure to control infection can both lead to death, minor differences in experimental protocols might influence the outcome of such experiments.…”
Section: Discussionmentioning
confidence: 98%
“…Adora2b signaling, we next performed studies to identify the role of Adora2b expressed on different cell types. As previous studies had implicated Adora2b signaling on endothelia (32) or epithelia (33) in organ inflammation, we used a transgenic mouse line with a floxed Adora2b gene (34) . Indeed, mice with genetic deletion of the Adora2b in tubular epithelia retained dipyridamole-mediated kidney protection from ischemia, indicating that ENT inhibition-mediated kidney protection is independent of Adora2b expression on tubular epithelia ( Figure 9, A-E).…”
Section: Figurementioning
confidence: 99%